ANALISIS PENGARUH RASIO PROFITABILITAS DAN ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM Studi pada Perusahaan yang Tercatat Aktif dalam LQ 45 di BEI Perioda 2008-2012 - Triwahyuningtyas, Triwahyuningtyas; Winarso, Beni Suhendra (Universitas Ahmad Dahlan, 2014)
This research aims to analyse the influence of the ratio of profitability and economic value added (EVA) company shares in return for the period 2008-2012 LQ 45. Data obtained from icmd and stock prices publication with a period of 2008-2012 .This research is a population of 45 companies and the total sample as many as 12 companies with sampling purposive past the stage. Dependent variable used in research is return stock, while the independent variable in the research is the ratio of profitability consisting of return on investment (ROI), net profit margin (NPM), gross profit margin ( gpm ) , earnings per share (EPS), and economic value added (EVA). Research result indicates that in the f roi, said the independent variable npm, gpm, eps, the yield on the first day, and eve three days before, and dd-4, influential jointly on the dependent variable (shares) and return on the first day because of return (0,032) H-3 ( 0,008 ) and H-4 ( 0,045 ) have a significance & it; 0.05.While this suggests that roi t have influence on the yield on the yield H+ 1 first day, and three days before, npm have influence on H-4 shares in return, return gpm have influence on the yield on the stocks return H+ 2 eps has an effect on the yield on the stocks return h and eva have influence on the yield on H-3 and H-2 of return